An updated knowledge of Black seed (Nigella sativa Linn.): Review of phytochemical constituents and pharmacological properties - Ahmad, Md Faruque (J Herb Med, 2021)
N. sativa (N. sativa) has been used since ancient times, when a scientific concept about the use of medicinal plants for the treatment of human illnesses and alleviation of their sufferings was yet to be developed. It has a strong religious significance as it is mentioned in the religious books of Islam and Christianity. In addition to its historical and religious significance, it is also mentioned in ancient medicine. It is widely used in traditional systems of medicine for a number of diseases including asthma, fever, bronchitis, cough, chest congestion, dizziness, paralysis, chronic headache, back pain and inflammation. The importance of this plant led the scientific community to carry out extensive phytochemical and biological investigations on N. sativa. Pharmacological studies on N. sativa have confirmed its antidiabetic, antitussive, anticancer, antioxidant, hepatoprotective, neuro-protective, gastroprotective, immunomodulator, analgesic, antimicrobial, anti-inflammatory, spasmolytic, and bronchodilator activity. The present review is an effort to explore the reported chemical composition and pharmacological activity of this plant. It will help as a reference for scientists, researchers, and other health professionals who are working with this plant and who need up to date knowledge about it.